English-Speaking Anxiety and Self-Esteem of Students at a Selected Private Junior High School in Minahasa Utara - Simanungkalit, Ate Gueen; Likuayang, Christin Claudia (LPPM Universitas Advent Indonesia, 2023)
Abstract This article reported a descriptive, correlational, and comparative quantitative research on English-speaking anxiety and self-esteem: description level of the two variables, relationship between them, and difference between 190 female and male respondent students at a selected private Junior High School in Minahasa Utara. To answer research questions, two questionnaires used to collect numeric data were as follows: the Horwitz’ Anxiety in Speaking English and Rosenberg’ conventional Self-esteem which were examined as valid and reliable after a statistical analysis through test of scale reliability. The findings revealed a high level of English-speaking anxiety and moderate level of self-esteem among the respondents; a statistically significant and negative relationship was found between English-speaking anxiety and self-esteem; and no significant difference were found between the female and male students’ anxiety in speaking English and their self-esteem. Nevertheless, the findings of this study were obviously deemed inconsistent with findings of previous studies conducted Indonesia and some Asian countries. Therefore, this study came up with recommendations that similar further studies be conducted in local context which could bring about more relevant, useful, and applicable implications. Keywords: English-speaking anxiety, gender difference, self-esteem